2021
DOI: 10.1177/2325967121992134
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable-Loop Devices Promote Graft Revascularization in the Femoral Tunnel After ACL Reconstruction: Comparison With Fixed-Loop Devices Using Magnetic Resonance Angiography

Abstract: Background: Hamstring tendon grafts are usually fixed in anterior cruciate ligament (ACL) reconstruction using either an adjustable-loop device (ALD) or a fixed-loop device (FLD). The contact area between the graft and the tunnel wall is different between the 2 devices. Purpose: To determine using magnetic resonance angiography (MRA) whether ALD and FLD result in different blood flow of the graft in the femoral tunnel during the early postoperative period. Study Design: Cohort study; Level of evidence, 3. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the ALDs were designed with an adjustable loop allowing for loop re-tensioning after graft insertion and adjustment of the loop’s length [ 39 ]. This provides surgical advantages that potentially lead to reduced bone removal [ 27 ], reduced femoral tunnel widening [ 14 , 25 ], and improved graft healing [ 23 ]. Biomechanical studies found ALDs to be inferior to FLDs in terms of maximum displacement after cyclic loading, ultimate load to failure, and stiffness [ 7 , 8 , 29 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ALDs were designed with an adjustable loop allowing for loop re-tensioning after graft insertion and adjustment of the loop’s length [ 39 ]. This provides surgical advantages that potentially lead to reduced bone removal [ 27 ], reduced femoral tunnel widening [ 14 , 25 ], and improved graft healing [ 23 ]. Biomechanical studies found ALDs to be inferior to FLDs in terms of maximum displacement after cyclic loading, ultimate load to failure, and stiffness [ 7 , 8 , 29 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge no clinical study has reported the postoperative tunnel lling of the RIGIDLOOP device. Moreover, recent studies have indicated that gap distances are positively correlated with postoperative femoral tunnel widening and that they may affect revascularization after ACLR based on CT and MRI image ndings [2,14,16,17,[19][20][21]. These ndings suggest that the large space may affect the prognosis of patients.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, investigators used magnetic resonance imaging (MRI) to evaluate the femoral tunnel and graft [2,3,16,17]. Ahmet.et al reported that the gap distance was 4.6 ± 0.3 mm and 9.5 ± 1.6 mm in the groups in which toggle loc with zip loop femoral xation ALDs and ENDOBUTTON CL xation loop devices were used, respectively [3].…”
Section: Discussionmentioning
confidence: 99%
“…ALDs have several advantages over FLDs. The tunnel size of ALDs is shorter, and drilling of exact tunnel length is not required as opposed to FLD, 34 resulting in a greater contract area (12% to 15%) between the superior tip of the graft (tendon) and the superior end of the tunnel wall in ALD than FLD. Kamitani et al.…”
Section: Discussionmentioning
confidence: 99%